2018
DOI: 10.1111/bjd.17341
|View full text |Cite
|
Sign up to set email alerts
|

Combined tetrahydrocannabinol and cannabidiol to treat pain in epidermolysis bullosa: a report of three cases

Abstract: This summary relates to https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 16 publications
(17 reference statements)
2
34
0
Order By: Relevance
“…Curiously however, whereas the SFN-mediated induction of keratin 16 partly depends on NRF2, the induction of keratin 17 is NRF2-independent [53]. Since topical and oral CBD have been used by EBS patients with promising results [22,54] our results provide a mechanistic explanation and support CBD as a promising option for the prevention of the pathological skin fragility occurring in EBS and for improving wound closure.…”
Section: Discussionmentioning
confidence: 64%
“…Curiously however, whereas the SFN-mediated induction of keratin 16 partly depends on NRF2, the induction of keratin 17 is NRF2-independent [53]. Since topical and oral CBD have been used by EBS patients with promising results [22,54] our results provide a mechanistic explanation and support CBD as a promising option for the prevention of the pathological skin fragility occurring in EBS and for improving wound closure.…”
Section: Discussionmentioning
confidence: 64%
“…The authors concluded that the effects might have been due to the anti-inflammatory activity of CBD, but in light of the above data, one can speculate that CBD might have beneficially modulated the keratin expression profile as well [ 183 ]. Likewise, in another small pilot study, three EB patients, who were prescribed pharmaceutical-grade sublingually administered cannabinoid-based medicine (CBM) comprising THC and CBD, reported improved pain scores, reduced pruritus and decreased overall analgesic drug intake [ 184 ]. Further studies are therefore invited to exploit putative therapeutic potential of the (endo)cannabinoid signaling in the clinical management of keratin diseases.…”
Section: Translational Potential Of the Cutaneous Cannabinoid Signmentioning
confidence: 99%
“…Research performed with adults with all subtypes of EB have shown pharmaceutical grade CBD-based medicines can improve pain scores, reduce pruritus and reduce overall analgesic drug intake. 35,36 There is no current recommendation for CBD use in paediatric patients with JEB.…”
Section: Novel Therapiesmentioning
confidence: 99%